Identifying and Mapping Ticks on Wild Boars from Romania - Ioan Cristian Dreghiciu; Mirela Imre; Diana Hoffman; Ion Oprescu; Vlad Iorgoni; Simona Giubega; Sorin Morariu; Marius Stelian Ilie (Animals)
Globally, due to climate change, urbanization, and the intensification of interactions between humans and animals, tick populations have increased, and areas where these arthropod vectors can develop and transmit diseases have expanded. Ixodidae ticks infect a wide variety of species and serve as major vectors for zoonotic pathogens of veterinary importance. This study aimed to identify and map ticks collected from boar tails in six Romanian counties. A total of 141 ticks were identified and differentiated on the basis of their morphological characteristics via stereomicroscopy and electron microscopy. Among the 141 ticks examined, five species, Ixodes ricinus, Haemaphysalis concinna, Haemaphysalis erinacei, Dermacentor reticulatus, and Dermacentor marginatus, were identified. The identification and mapping of ticks present on wild boars is beneficial for both veterinary and human medicine due to the pathogens they can transmit. The results of our study indicate that parasitism with different tick species in wildlife—in this case, wild boar—is present in the Romanian counties under study. This is one of the most recent tick identification and mapping studies. Tick parasitism represents a threat to the health of wild/domestic animals, and frequent monitoring is necessary.